Scandinavian & Baltic Europe - Bendure, Glenda; Friary, Ned; Cornwallis, Graeme; Kokker, Steve; Lucas, Clay (Melbourne Lonely Planet Publications, 2001)
An insispensable companion for the independent traveller, this comprehensive guide to Scandinavian and Baltic Europe covers Denmark, Estonia, the Faroe Islands, Finland, Iceland, Kaliningrad, Latvia, Lithuania, Norway, St. Petersburg and Sweden
Includes Index
Keywords: Guidebooks -- Scandinavia; Guidebooks -- Baltic States